Mediation of the effect of prenatal maternal smoking on time to natural menopause in daughters by birthweight-for-gestational-age z-score and breastfeeding duration: analysis of two UK birth cohorts born in 1958 and 1970 - Darina Peycheva; Leah Li; Mary Fewtrell; Richard Silverwood; Rebecca Hardy (BMC Women's Health)
Abstract Background Prenatal maternal smoking, lower birthweight, and shorter breastfeeding duration have all been associated with an earlier age at menopause in daughters. We estimated the extent to which birthweight-for-gestational-age z-score and breastfeeding duration mediate the effect of prenatal maternal smoking on time to natural menopause in daughters. Methods Using pooled data from two prospective birth cohort studies – the 1970 British Cohort Study (n = 3,878) followed-up to age 46 years and the 1958 National Child Development Study (n = 4,822) followed-up to age 50 years – we perform mediation analysis with inverse odds weighting implemented in Cox proportional-hazards models. Results Prenatal maternal smoking was associated with lower birthweight z-scores [β: -0.29; 95% CI -0.34, -0.24] and reduced breastfeeding duration [RRR< 1month: 0.90; 95% CI 0.79, 1.02; RRR≥ 1 month: 0.66; 95% CI 0.59, 0.73 relative to women who were never breastfed]. Greater z-score for birthweight [HR: 0.96; 95% CI 0.91, 1.01] and longer breastfeeding duration [HR≥ 1 month: 0.84; 95% CI 0.74, 0.96] were associated with lower hazards for earlier age at natural menopause. The total effect of prenatal maternal smoking on the time to natural menopause in daughters was estimated as a HR of 1.13 [95% CI 1.02, 1.24]. Birthweight z-score and breastfeeding duration jointly explained an estimated 14% of the total effect [HRNIE: 1.02; 95% CI 0.99, 1.05]. Conclusions The consequences of smoking during pregnancy on the earlier experience of natural menopause in daughters may partly be offset by intrauterine growth and longer breastfeeding duration to the extent that they mediate the risk of earlier menopause. However, since the extent of mediation by birthweight z-score and breastfeeding duration is small, other factors, including the direct effect of maternal smoking in utero, may play a more important role.